SYNOPTIC CONDITIONS FOR DANGEROUS FLUCTUATIONS OF SEA LEVEL IN THE PORTS OF ODESSA - Semerhei-Chumachenko Alina; Shepel Victoriya (World Science, 2024)
Rapid and significant changes in water levels can pose a danger to all marine vehicles, they can also affect coastal structures, accelerate coastal erosion processes and affect coastal ecosystems. Drops in the level of the Black Sea in the Odesa region occur mainly with northwesterly and westerly winds with an intensity 4-18 m/s in the cold half of the year, when a cyclonic vortex or an elongated baric basin formed over the Black Sea. At the same time, the interaction of the cyclone with the area of high pressure created a storm zone, where the northwest wind intensified. The storm surges were formed in the south and southeast direction of the wind at a speed of 8-18 m/s under the influence of a zone of large atmospheric pressure gradients between the trough over Eastern and Central Europe and the ridge of high pressure to the east of Ukraine.